Antibody responses to collagen peptides and streptococcal collagen-like 1 proteins in acute rheumatic fever patients. Issue 6 (29th June 2021) - Pilapitiya, Devaki H; Harris, Paul W R; Hanson-Manful, Paulina; McGregor, Reuben; Kowalczyk, Renata; Raynes, Jeremy M; Carlton, Lauren H; Dobson, Renwick C J; Baker, Michael G; Brimble, Margaret; Lukomski, Slawomir; Moreland, Nicole J
ABSTRACT: Acute rheumatic fever (ARF) is a serious post-infectious immune sequelae of Group A streptococcus (GAS). Pathogenesis remains poorly understood, including the events associated with collagen autoantibody generation. GAS express streptococcal collagen-like proteins (Scl) that contain a collagenous domain resembling human collagen. Here, the relationship between antibody reactivity to GAS Scl proteins and human collagen in ARF was investigated. Serum IgG specific for a representative Scl protein (Scl1.1) together with collagen-I and collagen-IV mimetic peptides were quantified in ARF patients ( n = 36) and healthy matched controls ( n = 36). Reactivity to Scl1.1 was significantly elevated in ARF compared to controls ( P < 0.0001) and this was mapped to the collagen-like region of the protein, rather than the N-terminal non-collagenous region. Reactivity to collagen-1 and collagen-IV peptides was also significantly elevated in ARF cases ( P < 0.001). However, there was no correlation between Scl1.1 and collagen peptide antibody binding, and hierarchical clustering of ARF cases by IgG reactivity showed two distinct clusters, with Scl1.1 antigens in one and collagen peptides in the other, demonstrating that collagen autoantibodies are not immunologically related to those targeting Scl1.1. Thus, anti-collagen antibodies in ARF appear to be generated as part of the autoreactivity process, independent of any mimicry with GAS collagen-like proteins. Abstract : Rheumatic fever is an autoimmune disease caused by a StrepA infection. Patients with rheumatic fever have antibodies that react with collagen, which may contribute to disease symptoms. But these rogue autoantibodies are not the same as the antibodies that react with parts of the StrepA bacteria, which resemble collagen. This means the rogue collagen antibodies seen in patients are most likely a consequence of the body's immune system malfunctioning and not directly caused by the StrepA infection.